An employee engagement framework for technical vocational education and training colleges in South Africa - Mmako, M; Schultz, C (South African Journal of Higher Education, 2016)
Employee engagement refers to what takes place when people are interested in a positive way and when they are excited about their jobs, exercise discretionary behaviour and are motivated to achieve high levels of performance. The present research therefore examined employee engagement of the academic staff in the Technical Vocational Education and Training (TVET) Colleges in South Africa. A quantitative design was used. In total, 2 054 academic staff completed the questionnaire. A self-administered 4-point Likert-type scale questionnaire was developed. The data was gathered and then analysed by using the Statistical Packages for the Social Sciences (SPSS). Descriptive statistics were used to present the findings. An employee engagement framework, which incorporates the main ideas of the article, suggests a new perspective about how to foster and manage employee engagement in today’s workplace is presented.